SOLID MAMMARY ADENOCARCINOMA IN A PET RABBIT (Oryctolagus cuniculus) - Mariana Ola Fonseca; Kamila Dantas Ruas; Mariana Ferreira Brito; Fernanda Cristina de Abreu Quintela Castro; Vida Emmanuelle de Deus Rosa; Haide Valeska Scheid; Tainá dos Santos Alberti; Clairton Marcolongo Pereira (UNESC em Revista, 2025)
Mammary gland tumors in domestic rabbits (Oryctolagus cuniculus) have been increasingly reported in clinical practice, and most cases exhibit malignant and biologically aggressive behavior. This report describes the clinicopathological features of solid mammary adenocarcinoma in an adult female rabbit presenting with a progressively enlarging and ulcerated mammary mass. The surgically excised nodule measured 6.2 × 5.0 × 3.0 cm and exhibited a white, multilobular appearance with friable areas upon sectioning. Histologically, the neoplasm was poorly demarcated, expansile, and infiltrative, composed of cuboidal to polygonal epithelial cells arranged in nests and compact solid sheets, showing marked pleomorphism, a high mitotic index (25 mitoses per 2.37 mm²), areas of necrosis, and pronounced anisocytosis, and anisokaryosis. Dilated mammary ducts and peritumoral inflammatory infiltrates were also noted. These findings support the diagnosis of solid mammary adenocarcinoma, a variant associated with aggressive biological behavior in rabbits. This case contributes to the growing body of knowledge regarding mammary neoplasia in pet lagomorphs and highlights the important diagnostic features for veterinary pathologists. Keywords: Rabbit, Oryctolagus cuniculus. Mammary neoplasia. Solid adenocarcinoma. Veterinary pathology. Histopathology.